The Burden and Effects of Cooking Fuels Usage on Women in Rural Areas: A Case Study of Afao-Ekiti, Nigeria - AKOMOLAFE, Kehinde John; YUSUF, Elizabeth (Journal of Environmental Management and Tourism, 2020)
This paper examines the burden and health effects of cooking fuels in Afao Ekiti, Nigeria. Primary data collected through the administration of structured questionnaires were used for the analysis. The results show that firewood is the fuel used intensively, and women trekked an average of 5 to 10km to collect it. Also, the result shows that most of the respondents who suffer from symptoms of diseases were women. In addition, most of the women who suffer from the reported cases of diseases were women from households who cooked with firewood or kerosene. In addition, most of the respondents were not willing to switch to the use of LPG for cooking because of its unavailability, cost of LPG, and the level of illiteracy in the use of LPG equipment. It is therefore recommended that there is the need for policy makers to embark on awareness campaign to educate rural dwellers on the proper use of LPG equipment, and on the health effects of various cooking fuel types.